Sur I’ adaptativite des maillages a base de quadrilateres Application a I’automatisation de calculs elements finis en elasticite 2D - Coorevits, Patrice; Pelle, Jean-Pierre; Rougeot, Philippe (European Journal of Computational Mechanics, 1994)
This paper gives a procedure of mesh adaptivity with quadrilateral elements. This procedure uses an error measure based on the constitutive relation, an efficient adaptive technique which automatically takes account of the singularities and the regions of stress concentration and a mesh generator of quadrilateral elements. We propose as application for 2D elastic structures the extension of automation of the finite element analysis which has been developed for triangular elements to the quadrilateral elements. The user describes the problem and the level of desired accuracy. The procedure then provides an approximate solution for a minimal computation cost with the respect of the desired accuracy. Examples are presented for discretizations using 4- or 8-node quadrilateral elements.